Discourse coherence: a case study of the French connector tandis que - Jadir, Mohammed (HERMES - Journal of Language and Communication in Business, 2000)
This paper aims to explore the role of connectors in the degree of discourse coherence. Starting from Dik’s (1997: ch. 18) discourse model, I examine the extent to which connectors can adequately be accounted for in the theory of Functional Grammar through the study of the French particle tandis que. At the semantic level, tandis que is characterized as a circumstantial satellite marker be it locally or in a more global scope. As for pragmatic functions, it is argued that the Parallel Focus function singled out by tandis que can also be assigned to more than one element of a parallel construction when the contrast is not a binary relation. The last part of my paper is devoted to the textual functions of the discourse marker tandis que, which is relevant as a coherence-promoting device in introducing Topics or in signalling discourse discontinuity.